COVID-19 risk perception moderates the relationships between health risk behaviors clustering and anxiety-depression comorbidity in adolescents - Shuman Tao; Yang Qu; Yi Zhang; Hong Gan; Xingyue Mou; Panfeng Zhou; Fangbiao Tao; Xiaoyan Wu (BMC Psychology)
Abstract Background Mental health problems were certainly widespread during the COVID-19 pandemic. The study aimed to examine the associations between clustering patterns of health risk behaviors (HRBs) and anxiety-depression comorbidity among Chinese adolescents, and further explore the moderating role of COVID-19 risk perception level in the associations. Methods A cross-sectional school-based study was conducted between April and May 2022 in Anhui Province, China. A self-administrated questionnaire was used to assess HRBs, anxiety-depression comorbidity, and COVID-19 risk perception. Latent Class Analysis was used to identify the clustering patterns of HRBs. The multinomial logistics regression models were used to explore the associations between clustering patterns of HRBs and anxiety-depression comorbidity. Furthermore, hierarchical multiple regression was used to analyze the moderating effect of COVID-19 risk perception level on the associations between the two. Results A total of 3 782 participants were analyzed. The prevalence of anxiety-depression comorbidity was 27.4%. HRBs clustering was grouped as category 1 (low-risk, 39.5%, n = 1 492), category 2 (unhealthy dietary patterns, 13.1%, n = 496), and category 3 (sleep insufficiency, 47.4%, n = 1 794). Unhealthy dietary patterns (OR = 2.10, 95%CI: 1.64–2.66) and sleep insufficiency (OR = 1.39, 95%CI: 1.17–1.66) were positively associated with anxiety-depression comorbidity. There was a positive moderating effect of COVID-19 risk perception on the relationships between clustering patterns of HRBs and anxiety-depression comorbidity (P<0.05). Conclusion COVID-19 risk perception enhances the positive association between clustering patterns of HRBs and anxiety-depression comorbidity symptoms in adolescents. Multidimensional risk factors should be warranted in the intervention programs for mental health among Chinese adolescents.